Social Support Mediates the Association between Disclosure of Suicide Attempt and Depression, Perceived Burdensomeness, and Thwarted Belongingness. Issue 4 (13th February 2020) - McClay, Michael M.; Brausch, Amy M.; O'Connor, Stephen S.
Abstract : Objective: Prior research has found disclosure of concealable stigmatized statuses, including suicide attempt survivorship, to be associated with positive mental health outcomes. This study sought to test the mediating effect of self‐reported social support on the association between disclosure of suicide attempt and suicide risk factors in a sample of undergraduate college students. Method: Data were analyzed from 149 undergraduate college students with a history of one or more suicide attempts. Three parallel mediation analyses tested the simultaneous mediating effect of family social support and peer social support on the association between suicide attempt disclosure and suicide risk factors. Results: Significant total indirect effects in all models indicated family social support and peer social support simultaneously mediated the association between disclosure of suicide attempt and depression, perceived burdensomeness, and thwarted belongingness. The indirect effect on thwarted belongingness via peer social support was stronger than the indirect effect via family social support. Conclusions: Disclosure of suicide attempt was associated with higher social support, which was associated with lower suicide risk factors. In a therapeutic context, it is important to consider social support when discussing disclosure of suicide attempt. Keywords: suicide, disclosure, attempt survivor, interpersonal needs, social support.